Tahadduts bi al-ni’mah Perspektif Quraish Shihab dalam Tafsir al-Misbah dan Relevansinya terhadap Pelaku Flexing - Labib, Abdulloh (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article aims to answer about the fate of Flexing perpetrators, which have recently been so prevalent on social media platforms that have received a lot of comments and criticism as a whole. This phoneme is caused by the lack of a deep understanding of religious knowledge, especially those related to Tahadduts bi al-Ni’mah. In this article, it is intended to describe the issue of flexing within the scope of the interpretation of the Qur'an, which will focus on the perspective of Quraish Shihab in the interpretation of al-Misbah. This study provides an understanding that the phenomenon of flexing Quraish Shihab's perspective is a negative act because it is considered irrelevant to Islamic religious rules when applied to people's social life.